Analisis Kesalahan Ejaan Yang Disempurnakan dan Diksi pada Surat Kabar - Nyi Raden Primawulan Meirani (Universitas Indraprasta PGRI, 2021)
The objective of the study is to analyze the Enhanced Spelling System errors and dictions used in the April 2021 issue of the Radar Karawang and Pasundan Expres. The method used is a qualitative method with an analysis description technique. The sources of data in this study are words, phrases, and sentences that misrepresent aspects of spelling and diction. Research has found 121 errors in the Radar newspaper including 80 spelling errors and 41 diction errors and 138 errors in the Pasundan express newspapers including 88 spelling errors and 50 diction errors. Misspelling errors found in the two newspapers are capital writing, italic writing, preposition writing, derivative writing, composite writing of words, particles, full stop, comma, hypen, and colon. The diction errors of the two newspapers are the use of abstract, synonyms, eufeumism, uneconomical sentences, plural meanings, miscontextual, unregulated words, grammatical forms, and familiar or unusual words. The dominant form of error in the Radar newspaper, which has the spelling aspect, is that foreword writing amounts to 18 words or 22.5 % of all 80 words, and from the prediction of conformity 32 words or 78.04 percent of the total 41 words. The dominant form of error in the post and express newspaper is the use of a coma of 26 errors or 29.54 percent of the 88 total while of the diction aspect is consistent with 23 errors or 46 % of the total 50 words. Key words: improved spelling, diction, newspapers